How Low Can Labor Law Go? Informalisation of Work and It’s Impact Upon Woman Workers in Indonesia - Tjandra, Surya; Tambunan, Rita Olivia (Indonesian Journal of International Law, 2008)
This article discuss about the development of labor law since the reformation and debating that non-formal job has been the main art of the labor law reformation from 1998, where made three new labor law, there are in 2000 and 2004. This article divided in three sections, the first is to explain about Indonesia and the labor law system in Indonesia, the second is discussing the impact of the new labor law, and the third is analyzing the impact from of the non-formal job, in this case are women and children in general, and in the East Java’s plantation project as a case.